Satisfying outcome of vagus nerve stimulation applied in the treatment of a patient with drug-resistant epilepsy caused by periventricular nodular heterotopia - Todorović, Stefan; Biševac, Boban; Lukić, Stevo; Ilić, Jovan; Aleksić, Dejan (Vojnosanitetski pregled, 2023)
Introduction. Periventricular nodular heterotopia (PNH) is a developmental malformation of the cerebral cortex characterized by abnormal migration of neurons into the cortical plate and is often associated with drug-resistant focal epilepsy. Case report. A 33-year-old female patient suffered from drug-resistant epilepsy, which was predominantly characterized by focal seizures, with occasional seizures that had a focal onset and progressed into bilateral tonic-clonic seizures. Magnetic resonance imaging showed bilateral heterotopic nodules in the occipital horns of the lateral brain ventricles. 18-Fluoro-deoxyglucose positron emission tomography – FDG-PET scan demonstrated a zone of reduced glucose metabolism on the right temporal region. Electroencephalogram suggested focal electrocortical activity on the temporo-parieto-occipital regions, predominantly on the right temporal side. The woman was treated with polytherapy (valproic acid, lamotrigine, levetiracetam, oxcarbazepine, pregabalin, clobazam, and lacosamide), but it did not affect the seizure frequency. Due to the bilateral localization of the heterotopic nodules, surgical treatment was not recommended. After a multidisciplinary assessment, we decided on vagus nerve stimulation (VNS) and achieved satisfying seizure control. Conclusion. Patients with PNH require multidisciplinary assessment and treatment, while in this report we have a case of a pa-tient in whom satisfying control of drug-resistant epilepsy was achieved after the implantation of the VNS device.